A note on global attractivity of the periodic solution for a model of hematopoiesis - Faria, Teresa (2019)
For a generalized periodic model of hematopoiesis, sufficient conditions for the global attractivity of its positive periodic solution are given, improving previous results in the literature. The effectiveness of the present criterion is illustrated by a numerical example.